Profitability and Balance Sheet Repair of Italian Banks - Jobst, Andreas (IMF Working Papers; Working Paper ;, 2016)
The profitability of Italian banks depends, among other factors, on the strength of the ongoing economic recovery, the stance of monetary policy, and the beneficial effects of current and past reforms, notably to address structural obstacles to resolving nonperforming loans (NPLs) and to foster banking sector consolidation. Improved profitability would enable banks to raise capital buffers and accelerate the cleanup of their balance sheets. This paper investigates quantitatively the current and prospective earnings capacity of Italian banks. A bottom-up analysis of the 15 largest Italian banks suggests that the system is on the whole profitable, but that there is significant heterogeneity across banks. Many banks should become more profitable as the economy recovers, but their capacity to lend depends on the size of their capital buffers. However, a number of smaller banks face profitability pressures, even under favorable assumptions. There is thus a need to push ahead decisively on cleaning up balance sheets, including through cost cutting and efficiency gains.